2015 WSGC Elijah High-Altitude Balloon Payload Project Final Report - Jensen, Benjamin Thomas (Proceedings of the Wisconsin Space Conference, 2016)
The purpose of this report is to discuss the research, development, and findings of several experiments performed on a high-altitude balloon payload platform. The team decided on the following five experiments to be performed during the flight: Oxygen Generation, Internal Heating, Speed of Sound Properties, Ozone Levels, and a new payload structure concept. The entire team was required to research and develop new skills to effectively design our experiments, including: Arduino programming, 3-D modeling/printing, soldering, launch equipment handling, and construction techniques. While the launch was successful, we did fall short of our overall goal in terms of data acquisition. The internship proved to be a rewarding introductory experience to real-world engineering. The project help us learn how to implement the entirety of the engineering process, using each person’s strengths to achieve an objective.